Reoffending among the child offenders in Malaysia: it's time to open our doors to theories underpinning diversionary measures - Ahmad, Nadzriah; Hamid, Abdul Ghafur@Khin Maung Sein; Wok, Saodah (Medwell Journals, 2016)
The increasing numbers of child offenders serving sentence in the institutions across Malaysia is worrying. However, the effectiveness of the current system in reforming and rehabilitating the child offenders remain an open question because of the rates of reoffending among child offenders. The objectives of this paper are to examine such issues by highlighting theories underpinning diversionary measures that call for the departure from the retributive system that is already entrenched in the juvenile justice system in Malaysia. A mixed quantitative and qualitative approach has been adopted to identify the rates of reoffending among 432 child offenders who participated in the study. The findings revealed that despite undertaking rehabilitative programmes in the institutions while serving sentence, the rates of child offenders who reoffended are increasing.